Immune Reactions following Cord Blood Transplantations in Adults - Hiroto Narimatsu (Stem Cells International)
Cord blood transplantation (CBT) is an attractive alternative therapy in adult patients with advanced hematological malignancies in whom matched donors are unavailable. However, the risk of complications, especially infections, post-CBT increases the mortality rates in these patients. Although the incidence of acute and chronic graft versus host disease (GVHD) post-CBT is lower than that following bone marrow transplantation and peripheral blood stem cell transplantation (SCT), the additional immunosuppressive therapy required to treat it could increase the mortality in these patients. Further, chronic GVHD following CBT is milder and responds better to treatment than that occurring after bone marrow transplants. Unlike bone marrow transplantation, the onset of GVHD is a positive prognostic indicator of overall survival in patients receiving CBT, due to the graft versus malignancy (GVM) effect. This paper focuses on the immune reactions following CBT and aims to elucidate a management strategy for acute and chronic GVHD.